Implementação de solução elemento-por-elemento em ambiente distribuído para o método dos elementos finitos - Ramon Pereira da Silva (1993)
An efficient finite element parallel solver has beem implemented on a virtual parallel machine using a cluster of workstations networked. The conjugate gradient method has been shown to be appropriate on the parallel implementation , and the matrices products involved in the derivation of the search direction vector have been carried out on a parallel basis. This approach has been proven to be feasible for this class of problems and promises to be a powerful solver on parallel architecture systems.